2012
DOI: 10.1002/jcu.21970
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical venous blood flow and its measurement in the human fetus

Abstract: In this review, we evaluate the published methodologies to describe a noninvasive technique for the quantitative assessment of umbilical venous blood flow in the human fetus. We identify a number of variations in the reported methodologies and address some of the common errors associated with Doppler assessment of umbilical venous flow volume. The potential role of umbilical venous flow volumetry in the management of intrauterine growth restriction is briefly evaluated including its utility and reliability in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 69 publications
1
28
0
Order By: Relevance
“…UVVF was calculated using previously published methods. 9,11,14 Methods of optimal UVVF calculation were employed: the umbilical…”
Section: Uvvf and Cco Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…UVVF was calculated using previously published methods. 9,11,14 Methods of optimal UVVF calculation were employed: the umbilical…”
Section: Uvvf and Cco Calculationmentioning
confidence: 99%
“…Umbilical venous volume flow (UVVF) is a validated, noninvasive method of measuring fetal placental blood flow and can be performed during routine fetal ultrasound. [9][10][11][12] Data suggests UVVF reflects placental rather than fetal characteristics: a study of monochorionic twins with selective intrauterine growth restriction demonstrated the discrepancy in in-utero UVVF reflected placental share at birth, rather than the discrepancy in birth weights. 13 To date, UVVF has not been measured in fetuses with CHD, and it is unknown whether flow through the placenta differs in these fetuses compared to normal.…”
Section: Introductionmentioning
confidence: 99%
“…Pulsatile waveform appears in the umbilical vein in starting of the first trimester of pregnancy but it completely disappears after 13 gestational weeks. Pulse in the umbilical vein is also associated with pathological conditions and is the most commonly used sign for measuring cardiac performance in umbilical vein [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The quantitative assessment of the absolute venous flow volume was conducted using methodologies previously described . They also normalised the venous flow volume per unit of fetal abdominal circumference.…”
Section: Introductionmentioning
confidence: 99%